Feasibility of Systematic Transesophageal Endoscopic Mediastinoscopy - Córdova, Henry; Martinez-Pallí, Graciela; Fernández-Esparrach, Gloria (The Thoracic and Cardiovascular Surgeon, 2013)
Thoracoscopy and mediastinoscopy are common procedures with painful incisions and prominent scars. Transesophageal endoscopic mediastinoscopy could reduce pain, improve cosmesis, and provide better access to the posterior mediastinal compartment, especially in patients with a complex mediastinum because of previous mediastinoscopy or with tracheostoma. We describe a new way to access the mediastinum through a natural orifice that provides excellent visualization of mediastinal structures.
Keywords: mediastinum (incl. mediastinoscopy); pneumothorax; thoracoscopy